2008
DOI: 10.1159/000113512
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Calcium-Binding Protein: Identification as a New Allergen of the Black Tiger Shrimp <i>Penaeus monodon</i>

Abstract: Background: Tropomyosin and arginine kinase have been identified as crustacean allergens. During purification of arginine kinase from black tiger shrimp Penaeus monodon, we found a new allergen of 20-kDa. Methods: A 20-kDa allergen was purified from the abdominal muscle of black tiger shrimp by salting-out, anion-exchange HPLC and reverse-phase HPLC. Following digestion of the 20-kDa allergen with lysyl endopeptidase, peptide fragments were isolated by reverse-phase HPLC, and 2 of them were sequenced. The 20-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 46 publications
(35 reference statements)
2
93
0
2
Order By: Relevance
“…Recently, several new shrimp allergens have been detected, including arginine kinase (Pen m 2, Lit v 2; 40 kDa) [9,10], sarcoplasmic calcium-binding protein (Lit v 4; 20 kDa) [11,12] and myosin light chain (Lit v 3; 20 kDa) [13]. By comparing the molecular weight of these allergens with those recognized by our patients on immunoblot analyses, it is possible to conclude that a proportion of our Pen a 1-negative patients was most probably reactive to AK, SCB or MLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several new shrimp allergens have been detected, including arginine kinase (Pen m 2, Lit v 2; 40 kDa) [9,10], sarcoplasmic calcium-binding protein (Lit v 4; 20 kDa) [11,12] and myosin light chain (Lit v 3; 20 kDa) [13]. By comparing the molecular weight of these allergens with those recognized by our patients on immunoblot analyses, it is possible to conclude that a proportion of our Pen a 1-negative patients was most probably reactive to AK, SCB or MLC.…”
Section: Discussionmentioning
confidence: 99%
“…Tropomyosin has been considered the major allergen in shrimp and molluscs and a minor allergen in other invertebrates ever since, and it has been reported that 85% of shrimp-allergic individuals show reactivity to this protein [8]. In recent years, several other shrimp allergens have been detected and characterized, including arginine kinase [9,10], sarcoplasmic calcium-binding protein [11,12] and myosin light chain [13], although little is known about the clinical relevance of these allergen proteins, and large population-based studies of shrimp allergy are missing. In the present study many Italian allergy centers participated in the detection and clinical characterization of shrimp-allergic subjects with the aim to investigate which are the shrimp allergens most frequently associated with clinically relevant shrimp allergy in this country.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoplasmic protein (A) SDS-PAGE Electrophoresis results of squid sarcoplasmic protein Several seafood sarcoplasmic proteins which can cause allergens is the sarcoplasmic calcium binding protein with 20 kDa molecular weight [20], hemocyanin with 72 kDa molecular weight [21], arginine kinase with 42 kDa molecular weight [22] and amylase [23]. Protein with a molecular weight of 42 kDa is suspected as arginine kinase that can bind to specific IgE antibodies in 4, 5 and 12 serums.…”
Section: Markermentioning
confidence: 99%
“…monodon, la arginina-cinasa (Pen m2) es capaz de unir anticuerpos IgE de 62 % de las personas alérgicas (42). Este alérgeno presenta 92 % de identidad en la secuencia de aminoácidos con Lit v 2 y Cra c 2 del camarón Crangon crangon, hecho que podría tener relevancia en la reacción cruzada entre estas especies (43)(44)(45).…”
Section: Arginina-cinasaunclassified
“…Este alérgeno se identificó en las especies de camarón L. vannamei, P. monodon y C. cangron, y en la nomenclatura oficial corresponde al grupo 4 (42,43,51 …”
Section: Proteína De Unión Al Calcio Del Sarcoplasma (Scbp)unclassified